Opportunities and challenges of low-dimensional hybrid metal halides in white light-emitting diodes. (18th August 2022) - Mo, Qionghua; Shi, Yingrui; Cai, Wensi; Zhao, Shuangyi; Ying, Yuansong; Zang, Zhigang
Abstract: Optically pumped white-light emitting diodes (WLEDs), including down conversion phosphors and blue/ultraviolet chips have attracted considerable attention in the solid-state lighting. However, commercial WLEDs contain massive rare-earth elements, which may suffer issues of unsustainability, potential price increasing due to insufficient supply. Thus, it is important to explore rare-earth-free light emitters with a broadband emission, a high photoluminescence quantum yield (PLQY) and an excellent stability. Recently, low-dimensional hybrid metal halides have received remarkable progress in WLEDs due to their high PLQY, ultra-broadband emission and easy synthetic procedures. In this review, the synthesis methods of low-dimensional hybrid metal halides are given followed by the discussions of their photoluminescence mechanisms. After that, low-dimensional hybrid metal halides with diversity colors including blue/blue-violet, green, yellow/orange, red/near-infrared are summarized. Specially, white light-emitting diodes based on low-dimensional metal hybrid halides will be reviewed. Finally, the perspective of the evolutions and challenges, the current limitations of the materials WLEDs are discussed, aiming to point of the inspirational outlook of their future development directions.